2023
DOI: 10.14309/crj.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Autoimmune Pancreatitis Unmasked by COVID-19 Vaccine

Abstract: Autoimmune pancreatitis is a rare fibro-inflammatory disease with 2 distinct subtypes of which each has their own clinical presentation, risk factors, and histopathological patterns. We present a case of newly diagnosed type 1 autoimmune pancreatitis in a symptomatic 54year-old man with stable ulcerative colitis 1 month after COVID-19 vaccination. Previous reports have indicated that vaccinations can trigger autoimmune disease in predisposed individuals. This case discusses the occurrence of autoimmune pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recent reports have indicated that COVID-19 vaccinations using mRNA or viral vector vaccines can trigger autoimmune diseases such as sialadenitis, autoimmune hepatitis (AIH), or autoimmune pancreatitis (AIP) in selected individuals [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. In the literature, several reports have treated the correlation between autoimmune pancreatitis and COVID-19 vaccination ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that COVID-19 vaccinations using mRNA or viral vector vaccines can trigger autoimmune diseases such as sialadenitis, autoimmune hepatitis (AIH), or autoimmune pancreatitis (AIP) in selected individuals [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. In the literature, several reports have treated the correlation between autoimmune pancreatitis and COVID-19 vaccination ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%